Birth prevalence of congenital heart defects in Western Australia, 1990–2016. (29th May 2021) - Hansen, Michele; Greenop, Kathryn; Yim, Deane; Ramsay, James; Thomas, Yarlalu; Baynam, Gareth S
Abstract : Aim: To describe the birth prevalence and characteristics of congenital heart defects in a geographically defined Australian population. Methods: This descriptive, population‐based study examined congenital heart defects in live births, stillbirths and pregnancy terminations ascertained by the Western Australian Register of Developmental Anomalies, 1990–2016. Birth prevalence (per 1000 births) was stratified by severity, known cause, maternal and birth characteristics, and primary diagnosis; and prevalence ratios were calculated for Aboriginal versus non‐Aboriginal births. Temporal trends in prevalence, diagnosis age and infant mortality were examined. Results: For births 1990–2010 (allowing 6 years for complete case ascertainment by 2016), 6419 cases were identified; prevalence was 11.5 per 1000 births (95% confidence interval (CI), 11.2–11.8). Severe defects were ascertained in 2.5 per 1000 births (95% CI 2.4–2.7). Most cases were liveborn (5842, 91.0%), and 28.9% had other birth defects. Prevalence was slightly higher in Aboriginal births (prevalence ratio 1.1; 95% CI 1.0–1.2); and the infant mortality rate more than doubled (13.4% vs. 5.8%, P  < 0.001). Prenatal diagnosis increased over time but, in remote areas, was significantly lower for Aboriginal versus non‐Aboriginal cases (3.1% vs. 9.3%; P  = 0.008). A cause was identified in 920 cases (14.3%), more often for severe defects (347, 24.4%); 63% of known causes were rare diseases. Congenital heart defects associated with fetal alcohol spectrum disorder were much more common in Aboriginal births (prevalence ratio 82; 95% CI 28–239). Conclusions: Earlier detection of congenital heart defects and improved survival has occurred over time, although discrepancies between ethnic groups and regions warrant further investigation and strategic action.